2015
DOI: 10.1016/j.cell.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Hypothalamic Network Dynamics for Appetitive and Consummatory Behaviors

Abstract: SUMMARY Optimally orchestrating complex behavioral states such as the pursuit and consumption of food is critical for an organism’s survival. The lateral hypothalamus (LH) is a neuroanatomical region essential for appetitive and consummatory behaviors, but whether individual neurons within the LH differentially contribute to these interconnected processes is unknown. Here we show that selective optogenetic stimulation of a molecularly defined subset of LH GABAergic (Vgat-expressing) neurons enhances both appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
498
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(569 citation statements)
references
References 57 publications
41
498
3
2
Order By: Relevance
“…These findings establish the GAD65 LH cells as key players in intra-LH information processing. Together with recent findings on roles of defined LH neurons in eating and arousal (7,36,38), our results substantiate specific LH circuits as orchestrators of key voluntary actions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings establish the GAD65 LH cells as key players in intra-LH information processing. Together with recent findings on roles of defined LH neurons in eating and arousal (7,36,38), our results substantiate specific LH circuits as orchestrators of key voluntary actions.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the previous studies of VGAT LH cells (36-39) likely targeted larger and more heterogeneous cell populations than our study, which was selective for GAD65 LH cells. This fact may explain why the VGAT LH cell stimulation drove different behaviors [increased eating and insignificant effect on locomotion (36,39)] than the GAD65 LH cell stimulation (increased locomotion and no significant effect on eating; Fig. 3 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral hypothalamus (LH) is a critical modulator of feeding (12,13). A previous study by Jennings et al demonstrated that GABAergic (Vgat-expressing) neurons in the LH are responsible for producing appetitive and consummatory behaviors (14). FXS animal models have lowered GABA subunit receptors, synthesis of GABA, GABAergic input to many regions of the brain, and increased catabolism of GABA (15,16).…”
Section: Neurobiology Of Fxs With Pwpmentioning
confidence: 99%
“…Historically, direct manipulation of specific cell populations was challenging, but recently developed optogenetic and chemogenetic approaches allow one to achieve this goal. In one recent example, Jennings et al (2015) used a combination of optogenetic, chemogenetic, and neuronal ablation procedures to show that activation of LH GABAergic neurons increased, and inhibition or ablation of GABAergic neurons decreased, appetitive (food-seeking) and consummatory (eating) behaviors.…”
Section: Introductionmentioning
confidence: 99%